Unveiling the mystery of hepatic epithelioid angiomyolipoma: A unique case report with literature review - Da Teng; Yue Xu; Qingtao Meng; Qingsong Yang (SAGE Open Medical Case Reports)
Hepatic epithelioid angiomyolipoma is a rare mesenchymal liver tumor within the perivascular epithelioid cell tumor family, known for its uncertain malignancy and potential for aggressive behavior. Clinical presentation, laboratory findings, and imaging results lack specificity, making pathological examination critical for definitive diagnosis. This case report presents a 61-year-old male patient with a single tumor in the right liver lobe, measuring approximately 101 mm × 99 mm. Initial imaging misdiagnosed the mass as hepatocellular carcinoma. Following multidisciplinary treatment discussions and subsequent tumor resection, histopathology and immunohistochemistry confirmed hepatic epithelioid angiomyolipoma. Accurate diagnosis of hepatic epithelioid angiomyolipoma is challenging, relying on histopathological examination and immunohistochemistry as diagnostic standards. Continuous monitoring of patients with hepatic epithelioid angiomyolipoma over an extended period is deemed essential. This report highlights the positive impact of multidisciplinary treatment in diagnosing and managing hepatic epithelioid angiomyolipoma.